THE INFLUENCE OF FLIPPED LEARNING MODELS USING THE BRAINSTORMING METHOD TO THE MATHEMATICAL PROBLEM SOLVING ABILITY - Nada Haristiani Barida; Sri Rahayu (MATEMATIKA DAN PEMBELAJARAN, 2022)
The purpose of this study is to determine the influence of flipped classroom learning models using  the brainstorming method  on mathematical problem solving ability in geometry transformation materials.  The population in this study was all class XI students of SMAN 1 Taman Sidoarjo.  Dari teknik purposive sampling obtained samples of class XI IPA 1 and XI IPA 2.  The data collection method in this study is the test and documentation method. Data analysis using normality, homogeneity, and t-tests. By data analysis using t-test obtained  with a significant level of 0.05. This shows that it is greater than the value , so in conclusion there is an influence of  the traditional flipped classroom type flipped learning model  using the brainstorming method on the ability to solve mathematical problems in geometry transformation material in class XI SMAN 1 Taman Sidoarjo.